2016
DOI: 10.1177/2056305116664216
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Sites, Friends, and Celebrities: The Roles of Social Comparison and Celebrity Involvement in Adolescents’ Body Image Dissatisfaction

Abstract: This study applies the social comparison theory to examine the effects of adolescents' engagement in comparison with friends and celebrities on social network sites (SNSs) on (a) their body image dissatisfaction (BID) and (b) their drive to be thin (DT) or muscular (DM). The study also examines celebrity involvement as an antecedent of the outcome variables. Data were collected through a survey of 1,059 adolescents in Singapore. Regression analyses indicate that SNSs use was related to adolescents' BID. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 68 publications
2
65
0
5
Order By: Relevance
“…Most households worldwide have home Internet access, and, in some countries, children, adolescents, and young adults identify social media sites as their primary online communication activity [20]. Given that both social media use and body dissatisfaction are pervasive among adolescent and young adult women, it is not surprising that media and body image research is expanding into this new media domain.…”
Section: The New Media: Social and Online Media And Their Inluence Onmentioning
confidence: 99%
“…Most households worldwide have home Internet access, and, in some countries, children, adolescents, and young adults identify social media sites as their primary online communication activity [20]. Given that both social media use and body dissatisfaction are pervasive among adolescent and young adult women, it is not surprising that media and body image research is expanding into this new media domain.…”
Section: The New Media: Social and Online Media And Their Inluence Onmentioning
confidence: 99%
“…In addition, a review of the literature by LeBourgeois and colleagues (2017) found "an adverse association between screen-based media consumption and sleep health" (p. S92). Further evidence supports an association between the use of social networking sites and body image dissatisfaction (Ho et al, 2016). Pew Research examining teens' social media experiences found that 45% of teens feel overwhelmed by the drama on social media, 43% feel pressure to post only content that makes them look good to others, and 26% say that using social media makes them feel worse about their own lives (Pew Research Center, 2018b).…”
Section: Benefits and Potential Harms Related To Social Media Usementioning
confidence: 99%
“…The literature presents an increasing number of documented negative consequences related to social media use (Ho et al, 2016;LeBourgeois et al, 2017;Lin et al, 2016;Pew Research Center, 2018;Primack et al, 2017;Uhls et al, 2017). Evidence suggests links between social media use and depression, anxiety, and social isolation (Lin et al, 2016;Primack et al, 2017).…”
Section: Benefits and Potential Harms Related To Social Media Usementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, adolescent girls' social media use has been shown to contribute to peer competition (Ferguson, Muñoz, Garza, & Galindo, 2014 Recent studies have suggested that there might be gender differences in SNS use. Females might be more interested in using SNS to maintain existing social relationships and to compare themselves with others (Haferkamp, Eimler, Papadakis, & Kruck, 2012;Hargittai & Hsieh, 2010;Ho, Lee, & Liao, 2016). In contrast, males might be more likely to use SNS to express their opinions and to make new relationships (Haferkamp, Eimler, Papadakis, & Kruck, 2012;Hargittai & Hsieh, 2010).…”
Section: Association Between Ds and Sns Usementioning
confidence: 99%